Inclusive Economic Development in Landak Regency A Descriptive Analysis of Economic Growth, Human Development, and Poverty - Lusia Sedati; Agusandi Agusandi; Stella Melin; Samuel Samuel (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to analyze the development of inclusive economic development in Landak Regency during the 2015-2024 period based on three main indicators: economic growth, human development, and poverty. This study employs a descriptive quantitative approach using secondary data obtained from Statistics Indonesia and various statistical publications related to Landak Regency. The analysis was conducted using descriptive statistics, annual development analysis, change analysis, and trend analysis without testing causal relationships or applying inferential statistical tests. The results show that economic growth in Landak Regency fluctuated throughout the study period. Economic growth reached 5.11 percent in 2015, contracted by -0.71 percent in 2020 due to the COVID-19 pandemic, and subsequently recovered to positive growth, reaching 4.54 percent in 2024. Human development demonstrated a consistent improvement, as reflected in the increase in the Human Development Index (HDI) from 64.12 in 2015 to 69.13 in 2024, representing an increase of 5.01 points. Meanwhile, the percentage of the poor population declined from 13.51 percent in 2015 to 8.98 percent in 2024, representing a decrease of 4.53 percentage points. Overall, Landak Regency demonstrated positive progress toward more inclusive economic development through improvements in human development and poverty reduction, although economic growth remained fluctuating and the benefits of development were not yet fully distributed evenly. Therefore, inclusive economic development should be directed toward strengthening growth based on leading economic sectors, improving human capital, expanding access to basic services, and increasing the productive capacity of poor and vulnerable communities.